IMPLEMENTASI KEBIJAKAN REHABILITASI NARKOBA DI BNN KOTA MOJOKERTO) - Nur Sandi, Bernardo; Wijaya, Dian; Yudha Utama, Jenny (MAJAPAHIT POLICY, 2022)
Narcotics and dangerous drugs (narcotics) in Indonesia in recent years have become a problemserious and reached an alarming condition and became a national problem. There is a need for socialization and rehabilitationcarried out by the government to eradicate drug users or dangerous drugs. To eradicate drug users,The government needs to make policies that will become the basis for the government to eradicate drug users. Through the Narcotics AgencyNationally (BNN), the government can reduce the number of drug users by achieving the eradication of all drug users inIndonesia. Mojokerto City BNN policy implementation as measured using Merilee S. Grindle's theory is related to sizesuccessful implementation of Mojokerto Mayor Regulation Number 12 of 2008 concerning the Mojokerto City Narcotics Agency which was followed byMojokerto City Government. Regional Regulation Number 25 of 2019 which then becomes a guideline for the creation of policy programsprevention of eradication of drug abuse and illicit trafficking (P4GN) and carried out by the City National Narcotics Agency (BNN)Mojokerto. In this research, the results were obtained that the implementation carried out by the Mojokerto City BNN was in accordance with the policyThere is. In an effort to rehabilitate people who have already become drug users, the Mojokerto City BNN is working hard torestore the enthusiasm of drug users when the rehabilitation period is over